2010
DOI: 10.1590/s0482-50042010000600005
|View full text |Cite
|
Sign up to set email alerts
|

Concomitância de fibromialgia em pacientes com espondilite anquilosante

Abstract: Introduction:Ankylosing spondylitis (AS) is a chronic inflammatory disease that affects the axial skeletal system, causing pain and functional incapacity. To measure the impact of AS on patient's life, questionnaires are used to assess disease activity (BASDAI); functional incapacity (BASFI); and quality of life (ASQoL). Fibromyalgia (FM) is one of the most common causes of generalized pain and can coexist with other diseases; it can be assessed by the Fibromyalgia Impact Questionnaire (FIQ). Few studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 20 publications
2
15
2
5
Order By: Relevance
“…Previous research has found that it is important to consider that the evaluation and diagnosis of SpA, particularly in women, can be delayed [35] and complicated by the presence of CWP. Symptoms such as chronic back pain, stiffness, and fatigue are common in patients with both SpA and FM, and can be interpreted, as indicating an increase in disease activity [26, 27, 36, 37]. Also difficulties in distinguishing fibromyalgia tender points and enthesitis sites in SpA have been reported [38], with an overlap of about 30% between the inflammatory back pain (IBP) criteria and the FM criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that it is important to consider that the evaluation and diagnosis of SpA, particularly in women, can be delayed [35] and complicated by the presence of CWP. Symptoms such as chronic back pain, stiffness, and fatigue are common in patients with both SpA and FM, and can be interpreted, as indicating an increase in disease activity [26, 27, 36, 37]. Also difficulties in distinguishing fibromyalgia tender points and enthesitis sites in SpA have been reported [38], with an overlap of about 30% between the inflammatory back pain (IBP) criteria and the FM criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Fibromyalgia is a syndrome of unknown etiology characterized by widespread chronic pain very often associated with fatigue, anxiety, depression and sleep disorders. Its prevalence in SpA ranges from 12.5% to 15% [141][142][143] and 2-7% in the general population. 144 In axial SpA patients, fibromyalgia reaches a prevalence of 25%.…”
Section: Fibromyalgiamentioning
confidence: 99%
“…Do total de artigos, 12 (N1, N2, N3, N6, N7, N9, N13, N14, N15, N16, N17, N19) possibilitaram a análise da população conforme o sexo, observandose maior prevalência do sexo masculino (KJEKEN et al, 2013;CONNOLLY;FITZPATRICK;O'SHEA, 2019;ALAMINO et al, 2011;LAW et al, 2018;WEBERS et al, 2016;DURCAN et al, 2012;FIGUEREDO et al, 2014;AZEVEDO et al, 2010;AZEVEDO et al, 2016;OLIVEIRA JUNIOR et al, 2015;AYDIN et al, 2015;BAE et al, 2019). Apesar de alguns dos estudos, como N13 e N16 (FIGUEREDO et al, 2014;OLIVEIRA JÚNIOR et al, 2015), N16 apontou que homens apresentam melhor status funcional que mulheres, correlacionando melhores níveis de funcionalidade (HAQ-DI) a melhores índices de qualidade de vida e de atividade da doença (BASDAI e CDAI) (OLIVEIRA JÚNIOR et al, 2015).…”
Section: Principais Debilitações Físicas Descritas Nos Artigos Selecionados Na Amostra Finalunclassified
“…trabalho, relatando uma piora no rendimento empregatício, sendo as áreas da concentração, carga horária de trabalho e afazeres domésticos as principais afetadas (CONNOLLY;FITZPATRICK;O'SHEA, 2019. O'SHEA, ) al., 2018WEBERS et al, 2016;DURCAN et al, 2012;AYDIN et al, 2015;YEN et al, 2017;AZEVEDO et al, 2010;BAE et al, 2019;PARK et al, 2019;VISHA et al, 2019;REINDERS;VAN WYK, 2012).Fonte: Elaborado pelos autores.…”
unclassified